THE DYNAMICS THAT AFFECT IMPLEMENTATION OF E-BANKING PRODUCTS AND SERVICES IN NIGERIA - Emiemu, ODUNEKA, Anagha; Effiong, BASSEY, Christian; Nnate, EKE, Chukwuma (IJRDO - Journal of Business Management, 2016)
The implementation of e-banking products and services is growing in Nigeria, but existing evidence points to the fact that the implementation level is still low. The market is growing at a for rate, particularly after the recent banking sector reconsolidation, but e-banking implementation is constrained seriously by poor ICT infrastructure, inadequate and unreliable electricity supply and telecommunication services, high level of illiteracy, and inadequate institutional support. More public and private investments are required for sustaining the growth and maintenance of e-banking infrastructure, and support services in Nigeria. Growth in private investment would however require more public policy effort at providing the enabling legislations and incentives.